Parents in Improving the Mental Health of Children and Adolescents Through Islamic Worship - Andriyani Andriyani; Masyitoh Masyitoh; Herwina Bahar; Raghib Filhaq; Munaya Fauziah (Indonesian Journal of Islam and Public Health, 2022)
In this modern era, children and adolescents are faced with challenges, so that in their development and growth they need guidance and control from people such as ways of thinking and acting. One way to control oneself is to understand religion. According to the 2018 Basic Health Research (Riskesdas), Indonesia currently has a mental disorder incidence rate of around 1 in 5 residents, meaning that around 20% of the population suffers from mental disorders. More than 19 million people over the age of 15 experience mental and emotional disorders, and more than 12 million people over the age of 15 experience depression. The purpose of this study was to examine some of the literature on the role of parents in improving the mental health of children and adolescents through Islamic worship. This study uses a study method which conducts research involving various kinds of information from libraries such as journals and theses. The results of research from various literature sources show that adolescents who understand worship and practice Islamic worship, are able to overcome problems in their lives, are grateful, are able to adapt to the environment, maintain relationships with the environment and God so that they tend to have good mental health standards. It can be concluded that adolescents who understand worship and practice Islamic worship are able to overcome problems in their lives and the role of parents is very important in improving mental health in children and adolescents.